PENGGUNAAN LIMBAH BATU MARMER DARI GUNUNG BATU NAITAPAN KABUPATEN TIMOR TENGAH SELATAN - Nauk, Sepriulus S.; Hunggurami, Elia; Bolla, Margareth E. (Jurnal Teknik Sipil, 2012)
The activity of marble mining at Mount Naitapan produces wastes such as powder and marble rocks. Efforts to utilize this waste as an alternative to aggregate in concrete mix. This research aims to discover the magnitude of compressive strength if aggregates in concrete that using marble waste as replacement. Specimens used is concrete cylinders. The marble waste used in three treatments of substitution they were substitution of marble powder by sand, marble rocks by the split stone, marble powder and marble rock by sand and split stone.The percentage of each substitution is 25%, 50%, 75%, 100%. The test result showed that for concrete with the substitution of marble powder by the sand and substitution of marble powder and marble rock by sand and split stone to substitute 75% increase while the compressive strength of 100% lower compressive strength. Substitution of marble rocks by the split stone had increased compressive strength.